The TRIM22-CDT2 axis is the key mediator of the p53-Rb signals in growth control of HPV-positive cervical carcinoma cells - Qing Zhou; Hongfei Yu; Anliang Dong; Jiani Yi; Jia Li; Xufan Li; Liyuan Zhou; Qiongzi Qiu; Bingjian Lu; Honghe Zhang; Weiguo Lu; Yi Sun; et al. (Neoplasia: An International Journal for Oncology Research, 2025)
Persistent infection with high-risk human papillomavirus (HPV) is the primary contributor to the development of cervical cancer. Although HPV oncoproteins E6 and E7 clearly trigger cervical tumorigenesis by inactivating p53 and Rb pathways, the downstream mediators of p53/Rb inactivation remain elusive. Here we report that CDT2, a subunit of Cullin-RING ligase 4 (CRL4), is significantly upregulated in cervical carcinoma tissues, which correlates with E6/E7 expression and poor patient survival. Mechanistically, E7-mediated Rb degradation upregulates E2F1, which in turn increases CDT2 transcription, whereas E6-mediated p53 degradation downregulates TRIM22, a novel E3 ligase for CDT2 degradation, leading to CDT2 accumulation to promote growth and survival of cervical cancer cells. Importantly, CDT2 depletion induces DNA aneuploidy and senescence via stabilization of histone lysine methyltransferase SET8, a CRL4CDT2 substrate, acting as a tumor suppressor. Collectively, the TRIM22-CDT2-SET8 axis is the key mediator of the p53/Rb signals in regulation of growth and survival of HPV-positive cervical carcinoma cells, Thus, CDT2 could serve as a prognostic biomarker and therapeutic target for these carcinomas.